2016
DOI: 10.1093/icvts/ivv397
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery for infective endocarditis in patients with intravenous drug use

Abstract: Cardiac surgery for infective endocarditis has acceptable early postoperative results among intravenous drug users. The 2- and 5-year survival were 79 and 59%, respectively. The number of reinfections was high within 2 years, as continued drug use seems to be a major challenge for this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 24 publications
(38 reference statements)
11
60
0
1
Order By: Relevance
“…The study revealed 75% of the IDUs were HCV positive. These results were in agreement with those reported by a study conducted on IE patients who were intravenous (I.V) addicts; they reported that 86% of the patients were HCV positive [32]. Our findings were in accordance with results reported by a study conducted by Ghosh et al, in which 91% of the patients had fever as the most prevalent symptom [33].…”
Section: Discussionsupporting
confidence: 93%
“…The study revealed 75% of the IDUs were HCV positive. These results were in agreement with those reported by a study conducted on IE patients who were intravenous (I.V) addicts; they reported that 86% of the patients were HCV positive [32]. Our findings were in accordance with results reported by a study conducted by Ghosh et al, in which 91% of the patients had fever as the most prevalent symptom [33].…”
Section: Discussionsupporting
confidence: 93%
“…20,36,45,46,47,48 These studies were limited by the small sample sizes of PWID and markedly different ages and comorbidities 20,49 of the 2 populations, which limits the conclusions that could be drawn. Notably, it has also been shown that PWID selected for surgery were more urgent cases (taken to the operating room within 24 hours) and more likely to have active infection, with the causative agent being S aureus, 50 suggesting a more unstable population.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, data regarding the outcomes of cardiovascular operations in this population are restricted mainly to reports based on single-institution experiences only. 10,[17][18][19][20][21] As such, a population-based overview of surgical outcomes among patients with OUD after various cardiovascular operations has not been previously reported. Therefore, the aims of this study were to use data from a large national database to (1) characterize the population of cardiac surgery patients with OUD and (2) investigate the association of underlying OUD with outcomes and resource utilization after cardiovascular operations.…”
mentioning
confidence: 99%